Inspiratory Muscle Training with an Electronic Device to Facilitate Weaning Ventilatory of a Patient with COVID-19. Issue 1 (April 2021) - Souza*, Leonardo Cordeiro de; ,; Souza, Amarildo Abreu de; Oliveira, Fernando da Franca Bastos de
No abstract available